2017
DOI: 10.3319/tao.2017.04.19.01
|View full text |Cite
|
Sign up to set email alerts
|

Pre-seismic strain anomalies and coseismic deformation of Meinong earthquake from continuous GPS

Abstract: High strain accumulation across the fold-and-thrust belt in SW Taiwan are revealed by the Continuous GPS (cGPS) from 2007 -2015. This high strain is generally accommodated by the major active structures in fold-and-thrust belt of western Foothills. In addition, the plastic deformation of mudstone in the Gutingkeng formation might play a crucial role for aseismic creeping. Furthermore, the distributed rightlateral shear zone, fault-related folding and aseismic creeping are also dominated from Lungchuan fault an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 73 publications
1
4
0
Order By: Relevance
“…Therefore, they concluded that the surface deformation of the Meinong earthquake was mainly controlled by the shallow structure (duplex structure; less than 10 km) instead of the deeper seismogenic fault. Moreover, according to Tsai et al (2017), the results related to the coseismic displacements of the Meinong earthquake (Figure 13) were also similar to those from Huang, Kuo, et al (2016). Based on the electronic supplement of Lee et al (2016), the NW-SE plane could not well produce the similar pattern of the GPS measurements (vertical component).…”
Section: Comparison Between This Study and Other Source Modelssupporting
confidence: 84%
See 1 more Smart Citation
“…Therefore, they concluded that the surface deformation of the Meinong earthquake was mainly controlled by the shallow structure (duplex structure; less than 10 km) instead of the deeper seismogenic fault. Moreover, according to Tsai et al (2017), the results related to the coseismic displacements of the Meinong earthquake (Figure 13) were also similar to those from Huang, Kuo, et al (2016). Based on the electronic supplement of Lee et al (2016), the NW-SE plane could not well produce the similar pattern of the GPS measurements (vertical component).…”
Section: Comparison Between This Study and Other Source Modelssupporting
confidence: 84%
“…Horizontal and vertical coseismic deformation of the Meinong earthquake adopted from Tsai et al (). The used GPS data are 5 days before and after earthquake.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Fu and Lee (2017) has reported significant changes in soil radon simultaneously at four stations in southern Taiwan approximately two weeks before the 2010 Jiasian earthquake. Furthermore, the significant rate-slow-down anomalies in cGPS pre-seismic baseline variations near the epicenter of the Meinong earthquake were also demonstrated in southern Taiwan (Tsai et al 2017). A 3D modelling work, i.e., mass flow-reactivegeomechanical transport is necessary in future.…”
Section: Resultsmentioning
confidence: 99%
“…The continuous GPS data show that the coseismic deformation in the Longci district (west side of Guanmiao district) had the largest vertical displacement of 100 mm and west horizontal displacement of 50 mm [38]. Based on the seismic data, GPS data and InSAR, Huang et al [22] presented a two-fault model, which included a 15-20-km depth main thrust fault and a 5-10-km depth shallower thrust fault.…”
Section: Study Areamentioning
confidence: 99%